The effects of oral protein on the absorption of intraduodenal levodopa and motor performance. Issue 9 (September 1989) - Frankel, J P; Kempster, P A; Bovingdon, M; Webster, R; Lees, A J; Stern, G M
Abstract : Four patients with levodopa induced fluctuations in motor performance were studied during the constant intraduodenal infusion of levodopa. The results confirm that steady plasma levodopa levels with stable motor control can be achieved. However, when patients were given oral protein loads, motor performance declined despite maintenance of plasma levodopa levels. These findings suggest that competition for levodopa carrier mediated transport by amino acids, is more important at the blood-brain barrier than across the gut mucosa; thereby possibly limiting the efficacy of long-term direct intraduodenal administration of levodopa.